TIDAK ADA PERBEDAAN BERAT BAYI LAHIR ANTARA IBU DIABETISI DAN IBU NON-DIABETISI - Emi Nur Cholidah; Bambang Wirjatmadi (Media Gizi Indonesia, 2015)
Diabetes mellitus is a metabolic multisystem disease characterized by hyperglycemia due to abnormalities in insulin  secretion and/or insulin work. In pregnancy, diabetes mellitus became one of the risk factor for infant’s high birth weight. The other potential factors are mother’sage, pre-pregnancy nutritional status, pregnancy weight gain, gestational age, and parity. Therefore, the research wanted to analyze the difference of birth weight between diabetic mother and non-diabetic mother. Comparative analytical method was used in this study with cross-sectional design.The sample in this study was 10 diabetic mothers and 10 non-diabetic mothers which was taken by simple random sampling in RSU Haji Surabaya. Independendent T-test was used to analyze the birth weight difference. The result showed that the proportion of hight birth weight were more prevalent in diabetic mothers (50%) than non-diabetic mothers (30%). Independent T-test analysis showed there was no difference in birth weight between diabetic mothers and non-diabetic mothers (p= 0,208). Further reseach is needed to understand birth weight determinant factors, particularly in diabetic mothers. Keywords: Birth Weight Infants, Diabetes mellitus, pregnancy, nutritional status